Optical properties of cometary particles collected by COSIMA: Assessing the differences between microscopic and macroscopic scales. (March 2020) - Langevin, Y.; Merouane, S.; Hilchenbach, M.; Vincendon, M.; Hornung, K.; Engrand, C.; Schulz, R.; Kissel, J.; Ryno, J.
Abstract: The COSIMA mass spectrometer on-board Rosetta was equipped with an optical microscope, Cosiscope, which identified several 10, 000 cometary particles collected on targets exposed during the orbital phase around the nucleus of comet 67P Churyumov-Gerasimenko. The median value of reflectance factors evaluated from Cosiscope images for large collected particles (~10.5% (Langevin et al., 2017), lies above the range of reflectance observed by the OSIRIS camera at a similar wavelength (5–7%, (Fornasier et al., 2015), but at much larger scales (a few 10 ​cm instead of a few 10 ​μm). In order to better understand this discrepancy, the assumptions underlying the derivation of reflectance factors have been reassessed using laboratory measurements of COSIMA targets and analogs of cometary particles. The approach of Langevin et al. is validated, but we consider that the uncertainty on reflectance factors was conservative. The reflectance factors are likely to lie in the lower half of the previously estimated range, which reduces (but does not eliminate) the discrepancy with OSIRIS albedos. The remaining discrepancy can be attributed primarily to the difference in scale (factor 10, 000 in pixel size between COSIMA and OSIRIS): Highlights: The COSIMA instrument on board ROSETTA has collected several 10, 000 cometary particles. Information on reflectance properties of collected particles has been obtained. A re-evaluation confirms that the mean reflectance of these particles is higher than that of the nucleus.